GC‒MS Analysis of Bioactive Compounds in Lime Leaf Ethanol Extract (Citrus amblycarpa (Hassk.) Ochse), and Its Potential as a Traditional Medicine Agents - I Nyoman Arsana; Ni Ketut Ayu Juliasih; A.A.A. Sauca Sunia Widyantari (Jurnal Penelitian Pendidikan IPA, 2024)
Lime (Citrus amblycarpa (Hassk.) Ochse) has been widely used in traditional medicine. However, only some studies have comprehensively revealed the content of leaves, including their use as candidate medicinal ingredients. This study aimed to analyze the active compounds of lime leaves through GC‒MS analysis and their benefits in traditional medicine. Experimental research with a laboratory approach is used. The implementation of research by analyzing the bioactive content of lime leaf ethanol extract using GC‒MS along with a comprehensive analysis related to its benefits as a traditional medicine agent. Data analysis using the Willey 7 Library database and descriptive analysis.  Using GC-MS showed that lime leaf ethanol extract contains 75 compound components dominated by 11 principal components, including citronellol, caryophyllene, hexadecanoic acid, ethyl ester, 1-heptatriacotanol, Phytol, ethyl 9,12,15-oate; methyl glycocholate, 3TMS derivative; 3,7-dimethyloct-6-en-1-yl stearate; ethyl iso-allocate; Rhopin; and tricyclo [20.8.0.0 (7,16)] triacontane, 1(22),7(16)-diepoxy-. Based on the findings of the content evaluation, the compound constituents of lime leaves have the potential to be developed as traditional remedies for both degenerative and infectious diseases. However, further research is needed precisely to identify the therapeutic effects exerted by using compounds on lime leaves.